Etablierung und Einsatz eines Enzymimmunassays für Testosteron-, Östrogen- und Glukokortikoidmetaboliten im Kot europäischer Wölfe (Canis lupus) mit Lagerungsexperiment - Wiese, Claudia (Tierärztliche Hochschule, 2014)
The wolf provokes a lot of controverse feelings and especially since it’s resettlement in Germany in 2000 there are disputable public opinions towards repopulation of the wolf. It is essential for monitoring wolves to find methods which obtain information about their number, reproduction status and health non-invasivly especially because the wolf is protected by law. By analysing fecal samples, via enzymeimmunoassay (EIA), it might be possible to obtain these information non-invasivly. Due to this purpose, the aim of this study was, to establish and use an Enzyme-linked Immunosorbent Assay to get valid information about the gonadal status (androgens and estrogens) and the activity of the hypothalamic-pituitary-adrenomedullary-axis (HPA) of wolves in captivity. Stimulating the HPA-axis by any stressor, results in the excretion of cortisol into the bloodstream, allowing conclusions from measuring fecal cortisol metabolites referring to individual stress level health status. To identify individual assignment of samples individual defacation was observed and protocolled. The assays used to validate androgens (5α-androstanolone, epiandrosterone und testosterone) have all been prooved to be valid to measure gonadal activity of European wolves because all of them showed significant differences between the intact and castrated wolves’ validation groups: testosterone-assays showed most significant results. Validating the estradiol-17β-assay, prooved to be not suitable to detect estrogen metabolites in the feces of European wolves. To validate a glucocorticoid assay an ACTH-test was performed in three European wolves, which methodically showed no valuable results. Instead we performed another ACTH-test with six German Shepherds and an anesthesia of a wolf was surveilled by collecting fecal samples during and after the intervention. After analysing these fecal samples, the corticosterone-assay (in comparison to: cortisol, 3α,11ß-dihydroxy-CM und 11-ketoetiocholanolon-tulln) showed to be best suitable to detect an HPA-Axis ...